2018
DOI: 10.1002/adbi.201700254
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the Uptake Characteristic of Inorganic Nanoparticles into Mammalian Cells—Insights Gained by TEM Investigations

Abstract: between individual uptake mechanisms for respective nanoparticle systems. Cells internalizing nanoparticles respond to the nanoparticles and different intracellular processes will be initiated, possibly resulting in the impairment of the cellular key functions. [4] Even though these investigations provide data with statistical relevance, they can merely provide an overall picture of the uptake mechanism, as issues of different uptake mechanisms in anisotropic nanoparticle suspensions are barely assessable. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 154 publications
(186 reference statements)
0
5
0
Order By: Relevance
“… 243 Inorganic NPs such as gold and heavy metal NPs are easily identified inside or outside the cell due to their high electron density that enhances imaging contrast. 240 Dobay et al investigated the subcellular distribution of AuNPs in lung epithelial cells by TEM. 245 They showed that AuNP uptake by cells occurs through different mechanisms including caveolae-dependent endocytosis.…”
Section: Methods To Study Endocytosismentioning
confidence: 99%
See 3 more Smart Citations
“… 243 Inorganic NPs such as gold and heavy metal NPs are easily identified inside or outside the cell due to their high electron density that enhances imaging contrast. 240 Dobay et al investigated the subcellular distribution of AuNPs in lung epithelial cells by TEM. 245 They showed that AuNP uptake by cells occurs through different mechanisms including caveolae-dependent endocytosis.…”
Section: Methods To Study Endocytosismentioning
confidence: 99%
“…EM is used to access the ultrastructural information of biological and non-biological specimens, providing a resolution in the nanometer range. 240 In particular, transmission electron microscopy (TEM) provides valuable insight into the localization of NPs in the cellular compartments. 241 Several drawbacks are associated with TEM, including the laborious sample preparation techniques, which includes fixation, dehydration, embedding, sectioning (o100 nm) and staining, [240][241][242] thus does not allow one to visualize dynamic events.…”
Section: Endocytic Markers and Microscopy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…90,91 Entry into the cell nucleus is typically limited to small NPs (<5 nm) and can be extended to 20 nm by employing an NLS peptide to assist with passage through the nuclear envelope. 92 Iron oxide NPs, in particular, tend to remain in the perinuclear region without further modification. 93,94 Our magnetofluorescent nano-hybrids cross both the cell and nucleus membranes without a need for an NLS tag, thus overcoming typical limitations of nanomaterials for nuclear targeting.…”
Section: Figure 1 Characterization Of Aptms-capped Fe3o4mentioning
confidence: 99%